Lime Treatment of Lake Texcoco Clays with Some Insights on the Application of Deep Mixing Columns. Issue 3 (March 2023) - Naik, Saureen R.; Akula, Pavan; Hariharan, Narain; Puppala, Anand J.; Little, Dallas N.; Castaneda, Javier
The soils across Lake Texcoco (LT) basin are notorious for the presence of highly compressible salt-affected lacustrine clays. The geological formation of the area accompanied by the unmonitored flow of water from Mexico City region has resulted in a unique sodium-rich clay that is highly plastic (plasticity index 200), and impermeable ( k 1.5 × 10 −9 m/s) and possesses low compressive strength (unconfined compressive strength < 10 kPa). Over the last few decades, the entire basin has settled at an average of 13.2 cm per year and will continue further with increased loads as a result of rapid urbanization. In planning a solid foundation for the airport, as well as developing the surrounding area, trial sections were built to analyze the effect of quicklime (CaO) on the natural clay s physical, chemical, and engineering properties through laboratory testing. The lab-scale investigations were accompanied with field measurements using the variable energy dynamic cone penetrometer (DCP) and plate load tests. Additionally, a numerical analysis of the effect of deep mixed columns (DMC) to reduce consolidation settlement was performed. The numerical analysis comprised of various DMC stabilizers, loading pressures, column lengths, and area replacement ratios. DMC lengths were observed to be the most dominant parameter to reduce consolidation settlements. Settlement reduction was more sensitive to the area replacement ratio for end-bearing columns, and to the loading pressures for floating columns. Based on the stabilizers evaluated, a combination lime and Portland cement performed the best across all loading pressures and column lengths. Other stabilizer combinations also had a remarkable effect on limiting the consolidation settlement.